The Development of Soil Moisture Control System based on Wireless Communication Technology for Off-Season Durian Production in Nopphitam District, Nakhon Si Thammarat Province, Thailand - Pettong, Wichan; Vongkrachang, Salila (Naresuan University Journal: Science and Technology (NUJST); Vol 28 No 1 (2020): January - March 2020DO - 10.14456/nujst.2020.4, 2020)
This study is a part of the research granted by the National Research Council of Thailand (NRCT). In this first stage, the study aimed to design and develop wireless communication system collecting data concerning soil moisture, light, temperature and humidity in the experimental off-season durian plantation. According to the experimental off-season durian plantation investigation, durian planting was divided into four phases. The site preparation phase started from January to April. From May to June was the controlling phase. Later, the pruning phase started from July to November and, finally, the harvesting phase was from December to January. Soil moisture analysis in those four periods found an average soil moisture content of 65 %. However, in April, soil water decreased by an average of 20 %. Therefore, irrigation was required to promote normal growth of durian. During the irrigation, temperature dropped and humidity increased by an average of 5%. All of these results will be used to develop soil moisture control system in the next stage. Keywords: Off-Season Durian, Soil Moisture, Wireless Communication, Measurement and Control System